Implanted electrhydraulic artificial heart - A. M. Shubladze; A. N. Baikov; N. A. Shvaryova; V. Ye. Tolpekin (Бюллетень сибирской медицины, 2010)
The problem of full-featured, high-efficiency replacement of the heart’s pumping ability with an artificial analog is urgent all over the world. The most promising model of an implanted artificial heart is now the model with the elecrohydraulic principle of operation. In the weight and overall dimensions and in the efficiency, this model can compete with the most popular Abiokor model of the artificial heart.